Population genomics of the eastern cottonwood (Populus deltoides). Issue 22 (10th October 2017) - Fahrenkrog, Annette M.; Neves, Leandro G.; Resende, Márcio F. R.; Dervinis, Christopher; Davenport, Ruth; Barbazuk, W. Brad; Kirst, Matias
Abstract: Despite its economic importance as a bioenergy crop and key role in riparian ecosystems, little is known about genetic diversity and adaptation of the eastern cottonwood ( Populus deltoides ). Here, we report the first population genomics study for this species, conducted on a sample of 425 unrelated individuals collected in 13 states of the southeastern United States. The trees were genotyped by targeted resequencing of 18, 153 genes and 23, 835 intergenic regions, followed by the identification of single nucleotide polymorphisms (SNPs). This natural P. deltoides population showed low levels of subpopulation differentiation ( F ST = 0.022–0.106), high genetic diversity (θW = 0.00100, π = 0.00170), a large effective population size ( N e ≈ 32, 900), and low to moderate levels of linkage disequilibrium. Additionally, genomewide scans for selection (Tajima's D ), subpopulation differentiation ( X T X ), and environmental association analyses with eleven climate variables carried out with two different methods (LFMM and BAYENV2) identified genes putatively involved in local adaptation. Interestingly, many of these genes were also identified as adaptation candidates in another poplar species, Populus trichocarpa, indicating possible convergent evolution. This study constitutes the first assessment of genetic diversity and local adaptation in P. deltoides throughout the southern part of its range, information we expect to be of use to guide management and breeding strategies for this species in future, especially in the face of climate change. Abstract : Forest tree species are especially vulnerable to the effects of climate change, with their survival and adaptation capacity determined in part by their genetic makeup. Applying a combination of population genomics methods to uncover signatures of selection and discover genetic markers associated with the environment, we identified a set of candidate genes for adaptation in the eastern cottonwood ( Populus deltoides ). This species is relevant as a feedstock for wood products and bioenergy, as well as a key component of riparian ecosystems in North America.